ANALISIS KETIMPANGAN PEMBANGUNAN ANTAR DAERAH SUMATERA UTARA BAGIAN TIMUR - Dewi Junisa (Universitas Negeri Medan, 2015)
This research purposes to analyse the building imbalance in every regencies/cities in East, North Sumatra : 1.Asahan regency, 2.Batu Bara regency,3. Labuhan Batu regency, 4.south Labuhan Batu regency, 5.north Labuhan Batu regency, 6.Tanjung Balai city to classify in every those districts. In this research uses Williamson’s Index approached method to quantify the building imbalance and tipology klassen’s analysis to classify economics growth in every districts. This analysis uses Bruto Regional Domestic Product data per capita at the constant price in 2000 and for North Sumatra in 2010-2012. This research, explains that 1. according to williamson’s index analysis the imbalance that happened in East-North Sumatra in 2011 decreasing between 1.7 being 1.47 and in 2012 increasing between 1.65 because it is far from the 0 ,so there is a high imbalance in East-North Sumatra. 2 according to tipology klassen’s analysis, there is no an advance and arise district in East- North Sumatra but including Batu Bara as an oppressed district as an advance one, still now the advance district is Labuhan Batu District, South Labuhan Batu and North Labuhan Batu and also Asahan and Tanjung Balai as the left behind district.